If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -3) + 6 = 4x + -4 Reorder the terms: 5(-3 + x) + 6 = 4x + -4 (-3 * 5 + x * 5) + 6 = 4x + -4 (-15 + 5x) + 6 = 4x + -4 Reorder the terms: -15 + 6 + 5x = 4x + -4 Combine like terms: -15 + 6 = -9 -9 + 5x = 4x + -4 Reorder the terms: -9 + 5x = -4 + 4x Solving -9 + 5x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -9 + 5x + -4x = -4 + 4x + -4x Combine like terms: 5x + -4x = 1x -9 + 1x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -9 + 1x = -4 + 0 -9 + 1x = -4 Add '9' to each side of the equation. -9 + 9 + 1x = -4 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = -4 + 9 1x = -4 + 9 Combine like terms: -4 + 9 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| 156-23/2 | | -5t^2+30t+2=12 | | 1/3x-12=5 | | 35x+25y=10250 | | 6/q= | | 4b+7=11 | | 19/4-7/3 | | 2x-5(4x+20)=32 | | 8y=16/7 | | Y=22x+1160 | | 8x-6=13x-21 | | 1/X-1/9=4/9-2/3X | | 2u/7=8 | | (50+7x)+3x=70 | | 6xy-2x+3cy-c= | | 8x-6=x+4 | | U^4w^4-u^4=0 | | 12x+(9x-3)-(10x-2)=12 | | 11/4-21/16 | | Y=11-6x/4 | | 5h+6(8h-1)= | | 4/9=2u | | 25d+50=175 | | 15x+5=14x+11 | | a=1/2bh;b=10,h=8 | | x+(x+1)=122-3(x+2) | | n/30-2=3 | | 7=12-5x+4y | | 7f-3=39 | | x-3/5=-1 | | 46-2=8 | | 3x^4-14x^2-24=0 |